Da’wa and politics: lived experiences of the female Islamists in Indonesia - Fuad, Ai Fatimah Nur (Contemporary Islam, 2020)
Stories about women activism in the Tarbiyah movement in Indonesia has gained scholarly attention. The existing literatures, however, tend to focus on the official discourses. This article discusses female members’ everyday experiences within the the liqo activity, as part of the Tarbiyah movement (circle of religious teaching). It examines the extent to which liqo members experience, receive, and practice the da’wa ideology designed by the Tarbiyah movement. It focuses on cadres’ stories about the lived experiences they have had through joining the liqo, with special reference to the female liqo group in Jakarta. Using ethnographic approach, data were collected through in-depth interviews with 26 female liqo members from a total of 45 interviewees and 15 observations of the liqo sessions. The study concludes that although the official form of religiosity, piety and political identity have been promoted by the Tarbiyah movement and its leaders, the experiences and practices of women revealed a heterogeneity and complexity of meanings of being in the liqo. This study attempts to contribute to the existing analysis of the da’wa (Islamic preaching and mission) and politics of a contemporary female Islamist movement with a case study of the Indonesian Tarbiyah movement.